Occult neoplasm in evisceration specimens - Al-Shamsi, Hanan N. (2012)
Purpose: To report the incidental surprise of an occult tumor in evisceration specimens, and to stress the need for careful preoperative evaluation for establishing the optimal surgical procedure Methods: A retrospective, clinicopathological case series of three patients who underwent evisceration for a blind and painful eye that turned out to harbor an intraocular tumor. The cases were collected by searching the indexed ocular pathology registry over a period of 25 years at a single tertiary eye care center in the Kingdom of Saudi Arabia. The medical records were reviewed for patient demographic data, initial clinical diagnosis, imaging, indication for evisceration, histopathology, post-evisceration management, and final outcome Results: The three cases represent 0.2% of the indexed evisceration specimens. None of them was previously known to have an ocular tumor. The indication for evisceration was a blind and painful eye secondary to the clinical impression of endogenous endophthalmitis, trauma, and scleritis with recurrent scleral perforation. Histopathology of the eviscerated tissue disclosed malignant uveal melanoma (MM), anaplastic carcinoma of the non-pigmented ciliary epithelium (ACNPCE), and intraocular mucoepidermoid carcinoma (MEC) respectively. Preoperative ultrasonography was not performed in the latter case and failed to detect a tumor in the other two cases. Post-evisceration work-up was negative for metastasis in all cases. Two patients subsequently underwent enucleation with or without orbital radiation and one patient (MEC) had total exenteration. The patient with the MM died 10 years after enucleation but the cause was undocumented. The case with MEC was lost to follow-up and that with ACNPCE was free of local recurrence or systemic metastasis after eight years of follow-up post enucleation Conclusions: Blind painful eyes may rarely harbor an occult malignancy that may masquerade as other clinical entities. The presence of an intraocular tumor should be ruled out prior to evisceration of any blind eye particularly with opaque media. Imaging studies may be inconclusive due to disorganization of the intraocular contents. Enucleation may be a better option than evisceration in such cases and may at least spare the patient additional surgical procedures